Jump and Lunge Frequencies Analysis during Men’s Single Badminton Matches: Implications on Physical Conditioning Training - Md Nadzalan, Ali; Fadhil Abdullah, Mohd; Janep, Mandra; Shahrul Azzfar, Mohamad; Abd Karim, Zulakbal; Jameelah Md Japilus, Siti (International Journal of Engineering and Technology, 2018)
The objective of this study is to determine the jump and lunge frequencies performed during men’s single badminton matches during world class level tournament. Players’ jump frequencies were calculated in the whole matches. Lunge frequencies were presented in the position performed in the court. The findings of this study will be beneficial as it can be used as a reference for developing training program besides technical and tactical plan during real matches.